Summer learning : research, policies, and programs - Borman, Geoffrey D.; Boulay, Matthew (L. Erlbaum Associates, 2004)
This book brings together up-to-date, research-based evidence concerning summer learning and provides descriptions and analyses of a range of summer school programs. The chapters present theory and data that explain both the phenomenon of summer learning.